The heat transfer mechanism study of three-tank latent heat storage system based on entransy theory. (June 2016) - Guo, Jiangfeng; Huai, Xiulan
Highlights: A three-tank latent heat storage system is investigated for solar energy with DSG. The mass flow rate of liquid LBE can be adjusted to specific heat of steam. There exist optimal mass flow rate ratio and mass flow rate of LBE. The optimal system performance is achieved at uniform temperature difference. Abstract: A three-tank latent heat storage system in which liquid lead–bismuth eutectic alloy (LBE) is used as sensible heat storage medium, and sodium nitrate is selected as the phase change material (PCM), is proposed in the present work. The performance of thermal storage system depends chiefly upon the heat transfer performance at superheated steam stage, and the mass flow rate of LBE can be adjustable to accommodate the specific heat change of water/steam. There exists an optimal mass flow rate ratio to maximize the performance of storage system. Generally, the more uniform the temperature difference distribution is, the higher the thermal performance of the storage system. The optimal mass flow rate of liquid LBE appears under constant mass flow rate ratio condition, in which the entransy and exergy rises of steam reach the maximum. The increasing number of transfer units at superheated steam stage improves the thermal storage performance monotonously. The exergy efficiency of this storage system runs at more than 80% through proper parameters setting.